Activating web networks through the experience of the Virtual University in Algeria - Djamila, Benlakreder (The International tax journal, 2026)
Science has recently witnessed an information revolution. Communication and media technologies were the decisive factor in these transformations and changes, which affected many fields, especially the scientific research sector. The activation of scientific research in the web is one of the reflections of technology in the educational field, and the concept of scientific research and the web is based on employing technical means in the educational field mainly. Through this new style, they receive lectures and lessons, conduct dialogues and communicate with professors without the need to travel to the university. Algeria has known this style of education and the new forms of these universities recently, with the entry of the Internet to it and making it available to institutions and individuals for their use in social and educational purposes in particular.